Clinicohematological correlation and chromosomal breakage analysis in suspected Fanconi anemia patients of India - Chowdhry, Mohit; Makroo, Raj Nath; Srivastava, Priyanka; Kumar, Manoj; Sharma, Sonika; Bhadauria, Preeti; Mahajan, Amita (Indian Journal of Medical and Paediatric Oncology, 2014)
Introduction: The management of patients with aplastic anemia, to an extent, depends on the etiology i.e., inherited or acquired. The classical Chromosomal breakage study involves detection of chromosomal breakage or aberrations (breaks, gaps, rearrangements, radials, exchanges, endoreduplications) in peripheral blood cells after culture with a T-cell mitogen and a DNA clastogenic (cross-linking) agent, such as diepoxybutane (DEB) or mitomycin C (MMC). The testing needs to be performed in laboratory with appropriate expertise in Fanconi Anemia testing. The present study was undertaken to find out the frequency of inherited aplastic anemia in North India. Materials and Methods: This study was carried out at the Department of Molecular Biology and Transplant Immunology, Indraprastha Apollo hospital, New Delhi. The study includes retrospective analysis of 528 aplastic anemia patients whose samples were tested at our department for Chromosomal breakage study during the period 2007 to 2011. Respective age and sex matched healthy controls were also processed for chromosomal breakage study. Patient′s habitat, clinical symptoms, differential blood count and history of drug exposure were documented for all patients referred to us, whereever available. Relative risk was estimated by odds ratio (OR) with 95% confidence interval (CI) in matched cases and controls. Conclusion: A significant increase in chromosomal breakages was seen in 13.1% patients. The survival data documented for 100 patients suggested 60% mortality.
Keywords: Aplastic anemia; chromosomal anomalies; chromosomal breakage studies; Fanconis anemia; mitomycin-C